Diferenciály osobních automobilů - Kozák, Ondřej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Tato práce obsahuje přehled diferenciálů osobních automobilů. V první části práce je uveden popis a rozdělení diferenciálů. Druhá část se věnuje diferenciálům současné produkce, a to zejména samosvorným diferenciálům s omezeným prokluzem.

This thesis contains a summary of automotive differentials and is divided into two parts. In the first part various sorts of differentials are described. The other part deals with differentials of current production, particularly limited slip differentials.
Developments of Car Drive Train
Keywords: Diferenciál; samosvorný diferenciál; uzávěrka diferenciálu; Differential; limited slip differential; differential lock